2022
DOI: 10.21873/anticanres.15876
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Chemotherapy as a Potential Treatment for Steroid-refractory Immune Effector Cell-associated Neurotoxicity Syndrome

Abstract: Background/Aim: Chimeric antigen receptor (CAR) T-cell therapy has revolutionized the treatment of various B-cell malignancies. However, it can cause serious adverse effects like immune effector cell-associated neurotoxicity syndrome (ICANS). ICANS is attributed to disruption of the blood-brain barrier due to inflammatory cytokines and increased levels of immune effector cells (IECs) in the cerebrospinal fluid (CSF). Corticosteroids and supportive management are the mainstays of ICANS treatment. However, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Due to the possibility that other cytokines, in addition to IL-1, could be implicated in the pathogenesis of ICANS, as well as the potential advantage of local control of CNS inflammation over systemic CAR-T cell depletion, treatment options such as IT administration of immunosuppressive drugs have been proposed. Clinical cases of IT therapy have been reported in the past (37, 41,42), and recently, small clinical studies have shown favorable outcomes in steroid-refractory ICANS (37) (Table 1). Yucebay F. et al reported a small clinical study investigating the IT administration of methotrexate 15mg, cytarabine 40mg, and hydrocortisone 50mg for the management of steroid-refractory or recurring high-grade ICANS following anti-CD19 CAR-T cell therapy.…”
Section: Discussionmentioning
confidence: 97%
“…Due to the possibility that other cytokines, in addition to IL-1, could be implicated in the pathogenesis of ICANS, as well as the potential advantage of local control of CNS inflammation over systemic CAR-T cell depletion, treatment options such as IT administration of immunosuppressive drugs have been proposed. Clinical cases of IT therapy have been reported in the past (37, 41,42), and recently, small clinical studies have shown favorable outcomes in steroid-refractory ICANS (37) (Table 1). Yucebay F. et al reported a small clinical study investigating the IT administration of methotrexate 15mg, cytarabine 40mg, and hydrocortisone 50mg for the management of steroid-refractory or recurring high-grade ICANS following anti-CD19 CAR-T cell therapy.…”
Section: Discussionmentioning
confidence: 97%
“…Treatment with glucocorticoids in association with supportive management represents the standard of care, despite the possibility that corticosteroids reduce the effectiveness of CAR-T cells remains a critical concern (64)(65)(66)(67).…”
Section: Strategies To Decrease Neurotoxicity Of Car-t Cell Therapymentioning
confidence: 99%
“…A few reports have demonstrated favorable outcome in steroidrefractory ICANS treated with intrathecal methotrexate (12 mg) and hydrocortisone (50 mg) (64,66). Asawa et al reported clinical improvement and rapid resolution of ICANS in two patients treated with intrathecal administration of methotrexate and hydrocortisone, both refractory to previous therapy with dexamethasone and tocilizumab (66).…”
Section: Strategies To Decrease Neurotoxicity Of Car-t Cell Therapymentioning
confidence: 99%
“…Current strategies typically employ systemic approaches, which may increase risk of immunosuppression in a highly vulnerable population. Limited case reports have described the use of intrathecal hydrocortisone (IT‐HC) ± chemotherapy for steroid‐refractory ICANS in adults with B‐cell lymphoma, leading to the reversal of ICANS symptoms 14–17 . There are limited data of this approach in pediatric patients with B‐ALL, as our institution is one of the few to incorporate this approach routinely 3,18,19 .…”
Section: Introductionmentioning
confidence: 99%